Reflections on music teacher professional development: Teacher-generated policies and practices. Issue 4 (2nd October 2019) - Johnson, Daniel C.; Marie Stanley, Ann; Ellie Falter, H.; Greene, Jennifer L. R.; Moore, Haley L.; Paparone, Stacy A.; Smith, Jacqueline C.; Snell II, Alden H.
Abstract: The purpose of this article is to make policy recommendations based on the authors' experiences with, and research about, reflective, differentiated, and teacher-generated music teacher professional development (PD). By doing so, we argue for a bottom-up process that capitalizes on our music teacher and music teacher educator expertise along with the research literature in music teacher PD. We explore music teachers' PD needs considering four career stages to explain how knowledge generated at each level informs our understanding of differentiated PD. From preservice music teachers and music teacher candidates, to in-service and veteran teachers, our discussion explores meaningful and effective ways to engage in deep, reflective thinking about the music teaching and learning process. Accordingly, we provide specific policy recommendations for music teachers at each career stage so that they might take greater ownership of their own learning, growth, and development through local, reflective, self-initiated, and differentiated PD opportunities.